Making Art Therapy Virtual: Integrating Virtual Reality Into Art Therapy With Adolescents - Shamri Zeevi, Liat (Frontiers in Psychology, 2021)
In recent years, the field of art therapy has sought to adapt traditional treatment approaches to today's innovative technological environments when working with adolescent “digital natives”. In their clinic, art therapists often struggle with lack of cooperation when treating adolescents during sessions. This article presents two case studies that explore how Virtual Reality technology can be combined with traditional art therapy to treat adolescents suffering from anxiety and social difficulties. It is suggested that this type of technology may lead to a better understanding of the needs of adolescents by adopting their vantage point and hence better outcomes.